The Role of Human Resource Management in Preventing Labor Law Violations at PT. Gajah Tunggal Tangerang - Rismanto, Caesar (The International Journal of Law Review and State Administration, 2025)
This study aims to analyze the role of Human Resource Management (HRM) in preventing labor law violations at PT. Gajah Tunggal Tangerang. Labor-related issues such as violations of workers’ rights, industrial disputes, and companies’ lack of understanding of labor regulations often hinder the creation of harmonious employment relations. This research adopts a qualitative approach with a descriptive method, utilizing interviews, observations, and document analysis related to company labor policies and HRM practices. The findings indicate that HRM plays a highly strategic role in integrating company policies with labor regulations through key functions such as legally compliant recruitment, proper drafting of employment contracts, fair performance management, and training programs on employees’ rights and obligations. In addition, internal monitoring and conflict mediation by the HR department have proven effective in preventing violations from escalating into legal disputes. This study concludes that implementing HRM in line with labor law not only reduces potential violations but also enhances productivity, employee loyalty, and overall well-being. Therefore, HRM serves as a crucial pillar in establishing fair, sustainable, and harmonious industrial relations at PT. Gajah Tunggal Tangerang.